Prognostic significance of the inhibitory-to-stimulatory immune checkpoint ratio in patients with breast cancer - Tang, Chuangang; Hu, Xiang; Hao, Dawei; Chen, Tao; Wang, Pei; Li, Changwen; Chen, Chengling; Li, Yongcheng; Hao, Xiaowen; Yuan, Zeng (Frontiers in Oncology, 2025)
BackgroundAccumulating evidences suggested that immune checkpoints (ICPs) played an important role in malignancies including breast cancer (BRCA). We aimed to investigate whether inhibitory-to-stimulatory immune checkpoint ratio (ISICPR) could be used as a prognostic marker for BRCA.MethodsBRCA patients were enrolled from The Cancer Genome Atlas (TCGA). Survival analysis was performed with Kaplan-Meier (KM) methods. X-tile was used to calculate the optimal cut-off values of ISICPRs. Univariate and multivariate Cox regression analysis were carried out to identify prognostic factors for BRCA patients. Tissue microarray was used to validate our findings.ResultsIn total, 586 BRCA patients were collected, including 104 cases of stage I, 330 of stage II, 139 of stage III, and 13 of stage IV. Univariate analysis showed that four ISICPRs (PDCD1/CD27 ratio, PDCD1/TNFSF4 ratio, IDO1/TMIGD2 ratio, and IDO1/TNFSF4 ratio) were significantly associated with the survival of BRCA patients. After adjusting for confounders, multivariate analysis indicated that only the IDO1/TMIGD2 ratio was an independent prognostic factor. The optimal cut-off values for the IDO1/TMIGD2 ratio were set at 4.4 and 6.3. Survival analysis indicated that the high-ratio group (ratio > 6.3) had a worse prognosis than both the low-ratio (ratio < 4.4) and medium-ratio group (4.4 < ratio < 6.3) (P < 0.001), which was further validated by BRCA tissue microarray.ConclusionsWe found that IDO1/TMIGD2 ratio was an independent prognostic factor for BRCA. On one hand, dual targeting of IDO1 and TMIGD2 may be a more effective therapeutic strategy for patients with a high IDO1/TMIGD2 ratio. On the other hand, ISICPR was a promising indicator with high clinical values and worthy of further promotion in other cancers.